Phosphorus and nitrogen derivatization as efficient route for improvement of lignin flame retardant action in PLA - Costes, Lucie; Laoutid, Fouad; Aguedo, Mario; Richel, Aurore; Brohez, Sylvain; Delvosalle, Christian; Dubois, Philippe (European polymer journal, 2016)
[Display omitted] •Effect of lignin incorporation on thermal degradation and fire behavior of PLA.•Phosphorus/nitrogen modification of lignin: enhancement of its FR effect in PLA.•Use of several innovative and original techniques for lignins characterization.•Gases from thermal decomposition of lignins analyzed by TGA-MS.•Gases from combustion of lignins analyzed by cone calorimeter-FTIR. The present study focuses on the use of lignin, which is the second most abundant constituent of the biomass, as sustainable flame retardant additive for polylactide (PLA). Indeed, thanks to its aromatic structure, lignin could be advantageously used, in polymeric matrices, as a char promotor agent that can allow some reduction of the combustion rate. An original and simple approach, based on a two-step phosphorus/nitrogen chemical modification, is proposed to enhance the flame retardant effect of lignin in PLA. This approach has been applied on two different lignins, i.e. kraft and organosolv lignins. The effect of the plant origin, extraction mode of lignin as well as it chemical modification on both its structure and properties was investigated by using several characterization techniques. Fire properties and thermal behavior of PLA composites containing 20 wt% of both untreated and treated lignins were characterized by using cone calorimeter, UL-94 and thermogravimetric analysis (TGA). Results showed that the incorporation of untreated lignins led to a flame retardant action in PLA thanks to the formation of char but also to a significant loss of the thermal stability of PLA and to an important decrease of its time to ignition. In contrast, both phosphorus/nitrogen chemically treated lignins were found to limit PLA thermal degradation during melt processing as well as during TG experiments and also to significantly improve fire retardant properties allowing to reach V0 classification at UL-94. In this paper we also deeply investigated the nature of the gases evolved during thermal decomposition of treated and untreated lignins by using TGA-Mass spectrometer and cone calorimeter – FTIR couplings.